TEETH CLIPPED-OUT IN JAVANESSE SLOW LORIS AND ITS PRESERVATION THROUGH ROOT CANAL TREATMENT - Guno, Bagus Brahmanto Aji; Kusuma, Randy; Taqwim, Muhammad Ihsannul (Buletin Veteriner Udayana, 2023)
Nycticebus javanicus or often called the Javan slow loris is one of Indonesia's endemic primates whose status is now in the critically endangered category because their numbers are decreasing. The illegal trade often causes serious problems for the health and survival of slow lorises in their natural habitat. There is a wrong perception that the teeth of slow lorises are poisonous, which makes illegal traders cut or even pull out the teeth of slow lorises indiscriminately. Slow lorises ( Nycticebus spp.) are obligate exudativators that gouge at tree bark with their teeth. In addition to functioning for the process of eating, slow loris teeth also function for defense mechanism and allogrooming. Amputation of dental crowns or crown fractures in slow lorises can be a serious problem. Slow lorises do not survive either slowly in rehabilitation centers due to changes in diet or even faster in their natural habitat when being released. Root canal treatment as an effort that can be taken to maintain the damaged or broken teeth, so as to prevent tooth from infection and maintain the function of slow loris teeth to survive in its natural habitat. The method of root canal treatment involves three fundamental components: root canal shaping, disinfection and obturation. Teeth restoration to be performed after obturation, using composite. Teeth that have been successfully treated provide an opportunity for slow lorises to express their natural behavior as well as in surviving in their natural habitat.